How large are present‐day heat flux variations across the surface of Mars?. Issue 12 (8th December 2016) - Plesa, A.‐C.; Grott, M.; Tosi, N.; Breuer, D.; Spohn, T.; Wieczorek, M. A.
Abstract: The first in situ Martian heat flux measurement to be carried out by the InSight Discovery‐class mission will provide an important baseline to constrain the present‐day heat budget of the planet and, in turn, the thermochemical evolution of its interior. In this study, we estimate the magnitude of surface heat flux heterogeneities in order to assess how the heat flux at the InSight landing site relates to the average heat flux of Mars. To this end, we model the thermal evolution of Mars in a 3‐D spherical geometry and investigate the resulting surface spatial variations of heat flux at the present day. Our models assume a fixed crust with a variable thickness as inferred from gravity and topography data and with radiogenic heat sources as obtained from gamma ray measurements of the surface. We test several mantle parameters and show that the present‐day surface heat flux pattern is dominated by the imposed crustal structure. The largest surface heat flux peak‐to peak variations lie between 17.2 and 49.9 mW m −2, with the highest values being associated with the occurrence of prominent mantle plumes. However, strong spatial variations introduced by such plumes remain narrowly confined to a few geographical regions and are unlikely to bias the InSight heat flux measurement. We estimated that the average surface heat flux varies between 23.2 and 27.3 mW m −2, while at the InSight location it lies between 18.8 and 24.2 mW m −2 . In most models, elastic lithosphere thickness values exceed 250 km at the north pole, while the south pole values lie well above 110 km. Key Points: Surface heat flux variations on Mars were investigated using numerical simulations of mantle convection in a 3‐D spherical geometry Heat flux anomalies introduced by mantle plumes remain confined to narrow regions and are unlikely to affect the InSight measurement The models predict north and south pole elastic lithosphere thicknesses that are consistent with the present‐day estimates